Analisis Penggunaan Diksi dan Framing Pada Media massa BBC News: Teori Hegemoni Gramsci - Puri, Diah Ryscha; Canda, Elis; Chairunisa, Hera; Indhira, Indhira; Pasaribu, Parlindungan; Silalahi, Selvina; Deo, Yohanna (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to analyze the use of diction and framing in the news text "Thai, Nepalese and other migrant workers killed and held hostage in attacks in Israel" written by BBC News mass media. The research method used is qualitative descriptive method. The data collection technique used is a listen and record technique. The result of this research is that the framing and use of diction used by BBC News makes Hamas look like the main perpetrator in attacks in Israel. This is in line with the theory of hegemony used, namely that there are interests of a group so that it influences and controls the world through news.